An Ayurvedic Review of Etiopathogenesis And Management of Amalapitta - Parashar, Love Kumar; singh, Shailendra Kumar; Kumar, Avadhesh (International Research Journal of Ayurveda & Yoga, 2021)
Amlapitta is one of the commonest diseases of Annavahasrotas (Gastrointestinal tract). Amlapitta (Hyperacidity) is a caused by excessive increase in the Amla guna of pitta Amlapitta (Hyperacidity) has been compound disease (caused by multiple factors). Amalapitta is one of the most common disease seen in the society. It is seen in all ages, all classes, and all community. According to Ayurveda All disorders are caused by vitiated Agni (digestive fire) and Amalapitta (Hyperacidity) is also one of them. Acharya Kashyap mentioned Amlapitta by the name of Suktaka while Madhav described Amalapitta as separate chapter. Acharya Charak has not mentioned Amlapitta as separate disease but described in Grahni Chikitsa as a Amaja Vikara which is caused by vitiated Agni (appetite). Amla pitta is mention since the Samhita period. Kulattha (Dolichus biflorus), Lavana Rasa, Viruddha Ahara (incompatible food) and other Pitta prokopaka factors are described as causative factors for Amla pitta. Amalapitta is a Sama- pittaja vikara so line of treatment is focused on application of Pittashamana drugs along with Panchkarma therapy and yoga. In Allopathic science, Hyperacidity refers to a set of symptoms caused by an imbalance between the acid secreting mechanism of the stomach and proximal intestine and the protective mechanisms that ensure their safety. Pathya-apathya (wholesome-unwholesome) plays very important role in management of Amalapitta.